PENGARUH MOTIVASI TERHADAP PENINGKATAN KEPUASAN KERJA PEGAWAI PADA KANTOR KECAMATAN BELITANG III OKU TIMUR - Darmanah, Darmanah; Hudawi, M. Nuh; Afrina, Iin; Zaidun, Zaidun (Jurnal Signaling, 2024)
To achieve the desired goals, the organization must strive to provide enthusiasm and motivation to its employees. This motivation is not only positive motivation but also negative motivation, other ways that an organization can do is by providing satisfaction to its employees. There you can see how the existing employees work. The organization must also understand what the complaints of its employees are, so that there will be no strikes which of course have a negative impact on the organization. The problem at the Belitang III OKU Timur District Office is how motivation affects Increasing Employee Job Satisfaction, and the goal achieved is to determine the effect of work motivation on increasing employee job satisfaction. The research method used is a quantitative approach with a causal research type. Primary data was obtained by distributing questionnaires to all employees of the Belitang III District Office. The data analysis technique used is simple linear regression analysis to test the effect of motivation on job satisfaction. In addition, validity, reliability, and classical assumption tests were carried out to ensure the quality of the data used in the study. The results showed that motivation has a positive and significant effect on employee job satisfaction. The coefficient of determination shows that most of the variation in job satisfaction can be explained by the motivation variable. This shows that increasing motivation, both from intrinsic and extrinsic factors, can significantly increase employee job satisfaction.